Critical Analysis of Values and Ethics of Leadership Effectiveness: Criticize the content - Al Halbusi, H.; Al Qaisi, E. (2017)
Currently the personal ethics and values of superiors and managers are matters to any organization. This paper aimed to conduct critical analysis personal values that influence the effectiveness of leadership. The author has selected a specific material related to the aim of the study and has analyzed it critically. The outcomes have revealed that, personal issues such as values, principles and ethics are essentials for any leader in the workplace that will be the guidance, also that make them perform more effectively rather than whose have less value and ethics. The consequences have discussed.